Numerical modelling of an alpine debris flow by considering bed entrainment - Qiao, Zhitian; Li, Tonglu; Simoni, Alessandro; Gregoretti, Carlo; Bernard, Martino; Wu, Shuangshuang; Shen, Wei; Berti, Matteo (Frontiers in Earth Science, 2023)
Numerical models have become a useful tool for predicting the potential risk caused by debris flows. Although a variety of numerical models have been proposed for the runout simulation of debris flows, the performances of these models in simulating specific events generally vary due to the difference in solving methods and the simulation of the entrainment/deposition processes. In this paper, two typical depth-averaged models have been used to analyze a well-documented debris-flow event that occurred in the Cancia basin on 23 July 2015. The simulations with and without bed entrainment are conducted to investigate the influence of this process on the runout behavior of the debris flow. Results show that the actual runout can be reproduced only by considering bed entrainment. If basal erosion is not taken into account, part of the debris mass deviates from the main path and both models predict unrealistic bank overflows not observed in the field. Moreover, the comparison between measured and simulated inundated areas shows that both models perform generally well in the terms of simulating the erosion-deposition pattern, although the DAN3D model predicts a greater lateral spreading and a thinner depositional thickness compared to Shen’s model. A simple numerical experiment obtains similar consequences and further illustrates the possible reasons that cause these differences.